A conceptual framework for the role of corporate social responsibility in Palestinian firm performance - Saleh, Mohammed W. A.; Abdul Latif, Rohaida; Abu Bakar, Fathiyyah (CSRC Publishing, 2018)
Objective: This research study has shed light on the perceptions of Corporate Social Responsibility (CSR) which identified in four dimensions of CSR including community, environmental, ethical, and consumer protection responsibilities.Methodology: This paper provides conceptual arguments that allow for better understanding of the role of CSR in the Palestinian society.Findings: The literature on CSR has increased substantially over the past decade, but existing research document mixed and inconclusive results on the role of CSR and firm performance.Implication: Although the link between CSR and firm performance have been studied, a significant research gap remains when considering the relationship between CSR and firm performance in the Palestinian context. This is because the CSR research has been neglected in the context of Palestine. For companies, this study proposes that they should put more efforts on enhancing the role of the CSR. Moreover, this study suggests for the management to re-think and re-strategize their CSR policies to improve their performance.